Socioeconomic factors impacting treatment delays in oral and oropharyngeal squamous cell carcinoma: a systematic review - Débora Rosana Alves Braga Silva Montagnoli; Vitória Ferreira Leite; Yasmim Silva Godoy; Carolina Castro Martins-Pfeifer; Johana Alejandra Moreno-Drada; Maria Cássia Ferreira Aguiar; Mauro Henrique Nogueira Guimarães Abreu; Renata de Castro Martins (Cadernos de Saúde Pública)
This systematic review investigates associations between socioeconomic factors and treatment delay in adults with oral and oropharyngeal squamous cell carcinoma (OOSCC). Observational studies were searched across five databases (PubMed, Scopus, Web of Science, Embase, and Virtual Health Library) and grey literature. No restrictions were imposed about language or year of publication. Risk of bias was analyzed using the Joanna Briggs Institute tool. The primary outcome was defined as the cut-off points of treatment delays, which was addressed by the studies included. The certainty of evidence was assessed following the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. In total, 10 retrospective cohort studies were included in the narrative synthesis. Type of insurance plan, sex, older ages, non-white patients, low education level, treatment in public or regional hospital, need for transition care, and living in regional/remote areas were factors associated with treatment delay for OOSCC. However, methodological limitations regarding the adjustment for confounders, the heterogeneity of the definition of delay (different cut-off points), socioeconomic variables, and the lack of eligible articles from different countries resulted in a very low certainty of evidence due to severe issues of bias, inconsistency, and indirectness according to the GRADE guidelines. The association between socioeconomic factors and OOSCC treatment delay is inconclusive by the available data. Given the complexity of the determinants of access to timely OOSCC treatment, further research is recommended in different countries.